Protease Enzyme Activity of Fungal Isolates from Avocado and Coconut Fleshes on Different pH and Temperature - Prapti Sedijani; Dinda Propita Lestari; Dewa Ayu Citra Rasmi; Kusmiyati Kusmiyati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Protease enzymes are widely applied in the industrial field. Protease enzymes have high economic prospects with unmet demand. This article describes protease activity of two fungi isolated from avocados and from coconuts fleshes that previously have shown a high lipolytic activity on pH 7 to pH 10. The protease test was performed on PDA medium supplemented with 1% of skim milk, and adjusted to pH 7, pH 8 and pH 9 and was incubated at room temperature and at 30°C. Protease activity was determined based on the clear zone around the colony observed on day two – day eight. The results showed that variations in pH and temperature had a significant effect on the protease activity. The highest protease activity of isolate from avocado and from coconut fleshes were observed at pH 7, room temperature and incubated for 24 hours, with a protease activity index of 0.36 and 0.31 respectively.